Comparing Point Source CO2 Emission Rate Estimates From Near‐Simultaneous OCO‐3 and EMIT Observations - R. R. Nelson; D. H. Cusworth; A. K. Thorpe; J. Kim; C. D. Elder; R. Nassar; J.‐P. Mastrogiacomo (Geophysical Research Letters)
Abstract Carbon dioxide (CO2) emissions from combustion sources are uncertain in many places across the globe. Here, we estimate CO2 emission rates from a small number of collocated observations from the Orbiting Carbon Observatory‐3 (OCO‐3) and the Earth Surface Mineral Dust Source Investigation (EMIT), both onboard the International Space Station (ISS). These near‐simultaneous measurements allow for an unprecedented comparison of two unique space‐based CO2 sensors over both isolated coal‐fired power plants and multi‐source scenes in China. We estimate CO2 emission rates using integrated mass enhancement and a Gaussian plume model. Where validation data is available, 15 of the 19 estimated emission rates have errors less than 37%. For the multi‐source scenes, EMIT can estimate emissions from individual facilities but its aggregate emissions are 42% lower than OCO‐3, likely because it cannot detect small sources or diffuse emissions. OCO‐3, with its excellent precision, may better constrain CO2 emissions over the entire scene.